Supporting religious exploratory students: Implications for academic advisors - Workman, Jamie; Ballinger, Gary (My University, 2019)
This paper was created using data from a larger study which examined first-year academic advising of exploratory students at a large public university. The project was conducted using grounded theory techniques, phenomenological perspective, and semi-structured interviewing. Themes emerged from the data and were categorized into one of the four S's of Schlossberg's transition theory. Religiosity and how it influenced student major and career decision making processes emerged as a notable theme for multiple students. Given this, the article focuses on how academic advisors can best support students who feel a deep connection between their faith and major and career decision making processes.
Keywords: exploratory college students, religiosity, Schlossberg’s transition theory